ANALYSIS OF SAIDI AND SAIFI STABILITY IN THE DISTRIBUTION SYSTEM AT PT. PLN (PERSERO) ULP FAKFAK - Naomi Lembang; Yurika Nantan Nantan; Rusliadi Rusliadi; Nurul Husnah; Yulianto La Elo (Jurnal Media Elektrik, 2024)
The increasing need for electrical energy requires the reliability of good electrical power distribution. Intentional or unintentional blackouts caused by electrical disturbances will certainly be detrimental to both PLN parties themselves. Several parameters that can be used as a reference in determining the reliability of a distribution system are by calculating SAIFI (System Average Interruption Frequency Index) which is an index calculation of the average number of disturbances during each month and SAIDI (System Average Interruption Duration Index) which is an index of the average duration of disruption to the system for one month. Analysis of the condition of the level of reliability of the distribution system at PT. PLN (Persero) ULP Fakfak aims to determine the monthly reliability of SAIDI and SAIFI in the distribution system at PT. PLN (Persero) ULP Fakfak whether it still meets the SAIDI and SAIFI target values at PT. PLN (Persero) ULP Fakfak.. The method used is a qualitative-descriptive approach. The results obtained are the SAIDI and SAIFI PT eligibility standard values. PLN (Persero) ULP Fakfak in the month standard used for SAIDI is the limit of 79.01 hours / plg - 308.00 hours / plg and the SAIFI standard is 0.56 times / plg - 1.86 times / plg. From the results of SAIDI calculations for 5 months from February - June, it can be seen that in May the SAIDI value was much better than the target set by PLN, namely 17.24 hours / plg. Meanwhile, SAIFI according to the calculation results was 0.16 times / home from 1.38 times / home in May set by PT. PLN (Persero) ULP Fakfak. Keywords: SAIDI, SAIFI, Reliability, Distribution Systems.